A MORPHO-FUNCTIONAL RECONSTRUCTION OF THE BRAIN OF NEOHYAENODON HORRIDUS (HYAENODONTIDAE, CREODONTA) BASED ON A NATURAL ENDOCRANIAL CAST - Saveliev S.V.; Lavrov A.V. (My University, 2001)
The study of the functional morphology and comparative anatomy of the brain's representations of the sensory systems, motor and associative centers of Neohyaenodon is based on a natural endocranial cast. Ethological and ecological peculiarities are reconstructed. The animal was relatively slow and not very agile, it was inclined to hunt prey by ambush. The angle of vision was about 340°, when the eyes fixed upon a target in front of the animal a sector of binocular vision reached 30-40°. Representation of the front legs in the neocortex was better developed than that of the hind legs. The tongue was very mobile allowing the animal to manipulate food in the mouth as well as to support activities connected with seizing prey. Vision was developed better than hearing and olfaction. The tail function represented in the motor sulcus of the frontal lobe by a special tubercle was probably used for intraspecific communication. Low aggression in Neohyaenodon and a relatively passive form of predation probably contributed to the extinction of the group during competition with more active Carnivora.